2022
DOI: 10.1088/1755-1315/997/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic co-digestion of pre-treated press mud and Molasses-based distillery wastewater enhanced biogas production

Abstract: With goals in determining the effect of diluting the distillery wastewater (DWW) and of varying the amount of DWW and press mud (PM), anaerobic co-digestion study was carried out at mesophilic condition in a 2-L Erlenmeyer flask, with a working volume of 800 mL for Batch 1 and 1500 mL for Batch 2 experiments. For Batch 1, two different ratios of DWW and tap water, with 2:3 and 3:2, were used to assess the effect of dilution on the methane yield, where same volumetric amount of PM was added. For Batch 2, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…[18] reported that as dilution increased, the biogas production also increased during the anaerobic digestion of cow dung. A similar result exposed that the highest dilution generated high methane [19].…”
Section: Model Equation Referencesmentioning
confidence: 67%
“…[18] reported that as dilution increased, the biogas production also increased during the anaerobic digestion of cow dung. A similar result exposed that the highest dilution generated high methane [19].…”
Section: Model Equation Referencesmentioning
confidence: 67%
“…The global landscape of waste management and sustainable energy generation has spurred an intensified exploration of innovative approaches to address these pressing challenges [1]. Anaerobic co-digestion, a novel biotechnological solution, has gained prominence as a promising method for simultaneously managing organic waste and producing renewable energy [2]. The pressing challenges of population growth, urbanization, and industrialization have accentuated the global demand for energy and aggravated the environmental burden of organic waste disposal [3], [4].…”
Section: Introductionmentioning
confidence: 99%